HUBUNGAN DUKUNGAN SOSIAL TEMAN SEBAYA DENGAN KEMAMPUAN BERSOSIALISASI PADA SISWA SMK NEGERI 3 MEDAN - Sri Wahyuni, Nini (Psychology Department Faculty of Psychology Universitas Medan Area, 2016)
This study aims to determine the relationship between social support peers in social skills to students of SMK Negeri 3 Medan. The subjects were students of SMK Negeri 3 Medan which numbered 60 people. Measuring instrument used is a Likert scale consisting of 36 items sociability (Î± = 0.897) and 46 items of peer social support (Î± = 0,929). Data analysis using techniques r Product Moment. Berdasdarkan data analysis, found that the hypothesis proposed in this study received, that there is a relationship between social support peers in social skills to students of SMK Negeri 3 Medan. This is evidenced by the value or coefficient of correlation ((r xy = 0.942, p = 0.000; p <0.05). Furthermore, seen from the calculation of hypothetical mean and the empirical mean and standard deviation is known that social support peers in social skills to students of SMK Negeri 3 field are low, where the average value of the empirical lower than the average value of the hypothetical.